High‐Field Electron‐Drift Velocity in n‐Type Modulation‐Doped GaAs0.96Bi0.04 Quantum Well Structure. Issue 11 (13th July 2022) - Aydın, Mustafa; Mutlu, Selman; Erol, Ayse; Puustinen, Janne; Hilska, Joonas; Guina, Mircea; Donmez, Omer
Abstract : The drift velocity ( v drift ) of electrons in an n‐type modulation‐doped GaAs0.96 Bi0.04 /Al0.15 Ga0.85 As quantum well (QW) structure is determined for electric fields ( F ) ranging from ≈0.4 to 3.58 kV cm −1 . The resulting v drift characteristic exhibited a linear increase and reached ≈6 × 10 6 cm s −1 at low electric fields then almost saturated with increasing electric field. The electron drift mobility is determined as 2265 cm 2 Vs −1 in the regime where the drift velocity is linear with respect to the electric field. The drift velocity saturates at ≈6.1 × 10 6 cm s −1 at the electric fields between ≈2.7 and 3.4 kV cm −1 . Saturation of the drift velocity is attributed to the transfer of the electrons from the QW layer (GaAs0.96 Bi0.04 ) with higher electron mobility to the barrier layer (Al0.15 Ga0.85 As) and satellite valley L‐valley with lower electron mobility, which initiates cooling of electrons via phonon scattering in the sample. Abstract : Herein, hot electron transport in n‐type modulation‐doped AlGaAs/GaAsBi is reported. Hot electron is generated by the applied pulsed external electric field. The drift velocity of the electron saturates at 6 × 10 6 cm s −1 . The drift mobility of the electron is 2265 cm 2 Vs −1 . Transferring the hot electron to the nearest L‐valley is more probable even in the higher‐energy barrier.